Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1136/annrheumdis-2011-200956
|View full text |Cite
|
Sign up to set email alerts
|

Golimumab in patients with active rheumatoid arthritis who have previous experience with tumour necrosis factor inhibitors: results of a long-term extension of the randomised, double-blind, placebo-controlled GO-AFTER study through week 160

Abstract: ObjectiveThe aim of this study was to assess long-term golimumab therapy in patients with rheumatoid arthritis (RA) who discontinued previous tumour necrosis factor alpha (TNFα) inhibitor(s) for any reason.MethodsResults through week 24 of this multicentre, randomised, double-blind, placebo-controlled study of active RA (≥4 tender, ≥4 swollen joints) were previously reported. Patients received placebo (Group 1), 50 mg golimumab (Group 2) or 100 mg golimumab (Group 3) subcutaneous injections every 4 weeks. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 24 publications
6
59
0
1
Order By: Relevance
“…Although direct comparisons with other anti-TNFs are limited by differences in study design and lack of head-to-head studies, the observed incidences of SAEs and fatalities in the RAPID 2 OLE were comparable to long-term studies of other anti-TNFs [19][20][21]. Similarly, the IR of serious infections reported in this study (4.1/ 100 PYs) is consistent with IRs reported from OLE studies of other anti-TNFs (ranging from 2.8/100 PYs to 6.4/100 PYs) [19,[22][23][24] and also with a recent pooled safety analysis of clinical CZP trials in RA (3.65/ 100 PYs) [25].…”
Section: Discussionmentioning
confidence: 77%
“…Although direct comparisons with other anti-TNFs are limited by differences in study design and lack of head-to-head studies, the observed incidences of SAEs and fatalities in the RAPID 2 OLE were comparable to long-term studies of other anti-TNFs [19][20][21]. Similarly, the IR of serious infections reported in this study (4.1/ 100 PYs) is consistent with IRs reported from OLE studies of other anti-TNFs (ranging from 2.8/100 PYs to 6.4/100 PYs) [19,[22][23][24] and also with a recent pooled safety analysis of clinical CZP trials in RA (3.65/ 100 PYs) [25].…”
Section: Discussionmentioning
confidence: 77%
“…Our current study was a pooled analysis of previously collected safety data from 5 large multicenter trials [8][9][10][11][12][13][14][15][16][17]18,19,20,21,22,23,24 , each of which was conducted according to the Declaration of Helsinki and the International Committee on Harmonisation Good Clinical Practices. Each of the phase 3 study protocols was approved by central or individual site institutional review boards/ethics committees, and all patients provided written informed consent prior to any study-related procedures.…”
Section: Methodsmentioning
confidence: 99%
“…No further ethical approval was required to conduct the additional data analyses reported herein. Patient entrance criteria and study designs for each trial have been reported [8][9][10][11][12][13][14][15][16][17]18,19,20,21,22,23,24 and are summarized in Table 1. Additionally, further details of each trial are available at clinicaltrials.gov (GO-BEFORE: NCT00264537, GO-FORWARD: NCT00264550, GO-AFTER: NCT00299546, GO-REVEAL: NCT00265096, GO-RAISE: NCT00265083).…”
Section: Methodsmentioning
confidence: 99%
“…8 GLM is a recent development in TNF antagonism and has been recently approved for the treatment of a variety of rheumatic inflammatory conditions, [3][4][5] with an acceptable safety profile, and remains the only TNF antagonist that has shown efficacy in patients refractory to other anti-TNF agents. 9 Due to GLM molecular structure, a fully human monoclonal antibody, GLM has a lower probability of developing neutralizing antibodies compared to other anti-TNF such as IFX, a chimeric monoclonal antibody, decreasing the risk of an allergic infusion reaction and any loss of efficacy. Although fully human, resistance to golimumab may potentially develop as well.…”
Section: Case Reportmentioning
confidence: 99%
“…To our knowledge, only two reports have been published related to GLM treatment in patients with ocular inflammation, one in idiopathic retinal vasculitis 9 and the other one in uveitis associated with juvenile idiopathic arthritis. 10 Although the follow-up after switch to golimumab was only 6 months, this case adds to the spectrum of uveitic conditions responsive to GLM.…”
Section: Case Reportmentioning
confidence: 99%